Efforts to Reduce Single Needle Sewing Machine Downtime Using the Define, Measure, Analyze, Improve and Control (DMAIC) Method on Line Hangers 1-6 at PT Dekatama Centra - Tina Martina; Vicken Anastasia; Ichsan Purnama; Afriani Kusumadewi (SAINTEKS : Jurnal Sain dan Teknik, 2026)
Downtime is a condition where a machine stops operating, disrupting the smooth production process. This study was conducted to reduce the downtime rate of single-needle sewing machines at PT Dekatama Centra line hanger 1-6 using the DMAIC (Define, Measure, Analyze, Improve, Control) method. This research is quantitative and descriptive and was conducted through historical data collection for January, direct observation in the production area of ??line hanger 1-6, and recording downtime data during April 2025. The Define stage was carried out by identifying the main problem in the form of high downtime rates of single-needle sewing machines on line hanger 1-6 at PT Dekatama Centra. This was done through direct observation and discussions with the production team at PT Dekatama Centra. Furthermore, in the Measure stage, downtime data was collected and classified based on the type of abnormality. A Pareto diagram was used to determine the frequency of the largest type of damage, namely congestion caused by the accumulation of dirt on the machine, which was then further analyzed in the Analyze stage using the 5 Why's method. The results of the analysis showed that the root cause of the dominant downtime problem came from the accumulation of dirt due to the absence of written work instructions set by the company to carry out scheduled maintenance on single-needle sewing machines. In the Improve phase, several efforts were made to reduce single-needle sewing machine downtime on line hanger 1-6 at PT Dekatama Centra, including regular machine cleaning by operators using the Autonomous Maintenance concept. This included the addition of single-needle sewing machine cleaning work instructions and the dissemination of procedures to operators in early May 2025. The results of the implementation in May showed a decrease in total downtime, from 4,616 minutes in April 2025 before the improvement, to 4,184 minutes in May 2025. Based on these data, it can be concluded that single-needle sewing machine downtime on line hanger 1-6 at PT Dekatama Centra decreased by 9.4% after the improvements. In the Control phase, control measures were developed in the form of a daily maintenance checklist, filled out directly by the line manager and validated by the supervisor to ensure continuous and well-monitored improvements. This research demonstrates that the DMAIC method can be effectively applied to reduce single-needle sewing machine downtime through a systematic, data-driven approach and root cause analysis. The implementation results show a significant reduction in downtime after improvements in work methods and machine maintenance habits.